Health of the City and Health in the City - Tkacheva, Marina (project baikal, 2019)
The participants of the discussion spoke about many aspects of a healthy life in the city. They featured town-planning, psychological and medical issues of health. They touched upon changes in the city master plan and the principles of its elaboration, urban green areas and the impact of civil society and public discussions on the strategy of city development.